The determinants of idiosyncratic volatility in Indonesia banking industries - Amrie Firmansyah; Pardomuan Sihombing; Sri Yani Kusumastuti (University of Merdeka Malang, 2020)
This study aims to examine the determinants of idiosyncratic volatility. This study uses firm fundamentals, institutional ownership, interest rates as idiosyncratic volatility determinants. The firm fundamentals of this study are represented by firm size, profitability, operating performances, dividend policy, and price to earnings ratio. Institutional ownership represents the ownership of the company’s shares by financial companies. The interest rates are represented by 3-month bank deposit rates for one year. The research method uses a quantitative approach with secondary data. Hypothesis examining is conducted by panel data regression analysis. By using a purposive sampling method, the company selected is 24 banking sector companies with observation time from 2012 up to 2018. Thus, the total sample in this research amounted to 168 firm-year. The result of the study suggests that firm size, price-earnings ratio, dividend policy, profitability, and interest rates are negatively associated with idiosyncratic volatility. However, operating performance and institutional ownership are not associated with idiosyncratic volatility.JEL Classification: E43, G21, G32 How to Cite:Firmansyah, A., Sihombing, P., Kusumastuti, S. Y. (2020). The determinants of idiosyncratic volatility in Indonesia banking industries. Jurnal Keuangan dan Perbankan, 24(2), 175-188.DOI: https://doi.org/10.26905/jkdp.v24i2.3851